Predictors of the development of acute pneumonia in children of early age - Krainia, H.; Крайня, Ганна Вікторівна (My University, 2020)
The analysis of the anamnestic data of life and disease, as well as indicators of the content of antimicrobial peptides in the blood serum of children of early age made it possible to identify the most significant predictors of the risk of developing acute pneumonia. The effect on modified factors will prevent the development of the disease and increase the effectiveness of therapeutic measures for this children.
Keywords: pneumonia; children of early age